2017
DOI: 10.7150/ijbs.18890
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-7 Mediates Bystander Autophagy in Lung after Focal Brain Irradiation in Mice

Abstract: This study investigated whether exosomal microRNA-7 (miR-7) mediates lung bystander autophagy after focal brain irradiation in mice. After 10 Gy or sham irradiation of mice brains, lung tissues were extracted for the detection of autophagy markers by immunohistochemistry, western blotting, and quantitative real-time reverse transcription PCR (qRT-PCR), meanwhile the brains were dissociated, the neuron/astrocyte/microglia/oligodendrocyte were isolated, and the miR-7 expression in each population were detected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Finally, LC3B and p62 western-blotting further corroborated our findings ( Figure S1C ). We concluded that miR-7-5p, through the binding and downregulation of potentially several targeted mRNAs, is a potent regulator of cell viability and cell autophagy in Karpas-299 cells, as previously described in other studies [ 55 , 56 , 57 , 58 ].…”
Section: Resultssupporting
confidence: 84%
“…Finally, LC3B and p62 western-blotting further corroborated our findings ( Figure S1C ). We concluded that miR-7-5p, through the binding and downregulation of potentially several targeted mRNAs, is a potent regulator of cell viability and cell autophagy in Karpas-299 cells, as previously described in other studies [ 55 , 56 , 57 , 58 ].…”
Section: Resultssupporting
confidence: 84%
“…These results may be interpreted that MEG3 acted as a sponge of miR-7-5p to regulate the activation of downstream mTOR signalling, and in turn, modulate cardiomyocytes autophagy. MiR-7-5P is an important regulator in cell autophagy in various cell type [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes containing miR-7-5p proved to be internalized by non-irradiated BEP2D cells which, therefore, entered in autophagy, by reduced expression of EGFR, a known target of miR-7-5p ( 174 ). A distant bystander effect was also demonstrated in vivo ( 175 ). After focal brain irradiation of mice, exosomes were obtained from irradiated astrocytes and found to express high levels of miR-7.…”
Section: Biological Functions Of Exosomes In Prostate Cancermentioning
confidence: 92%
“…After focal brain irradiation of mice, exosomes were obtained from irradiated astrocytes and found to express high levels of miR-7. Injected into the tail vein of non-irradiated mice, they were able to induce autophagy of lung tissues by directly targeting Bcl-2 ( 175 ). Other miRs may have similar effects, such as miR-145, which proved to sensitize PCa cells to radiation ( 176 ).…”
Section: Biological Functions Of Exosomes In Prostate Cancermentioning
confidence: 99%